Intervenção fonoaudiológica com foco na comunicação televisiva: efeito de uma proposta com graduandos de jornalismo - Santos, Telma Dias dos (2016)
the journalistic communication on television and the viewer have changed and therefore the media companies have demanded more versatility of journalists. As a result, the performance of the speech therapist has been transformed and expanded, as we see the need for it to be present in the formation of the journalist. It was in view of this new reality and demand that intervention research for subjects in vocational training offered. Objective: To evaluate the effect of an intervention proposal focusing on professional communication in television for undergraduate journalism students. Method: The sample consisted of 23 journalism students, 12 women and 11 men, aged between 18 and 21 years. The Speech therapy intervention had eight meetings lasting four hours each more the recording a video with the same news before and after the intervention. The evaluation of the communicative performance of students was carried out by 75 judges viewers with the videos pairs and they chose the best video. This choice was justified by the allocation of features divided into three main points were these: body, speech and interpretation / emotional. Results: The majority (91.3%) of the students showed a better communicative performance in the video after the intervention according to the judges. The parameters related to aspects of emotional / interpretation were those who had more cited characteristics. Those with the highest number were more natural followed by safer, more pleasant and more confident in video after intervention. Regarding the most frequently cited characteristics of speech aspect was found in citation order: articulation, pauses, emphasis and speech rate. The aspects were: body posture, body movement and gestures. Final considerations: the speech therapy program focusing on professional communication in television promoted improvement in communication performance of most journalism students of the sample studied. The aspects that the most mentioned judges to justify the improvement was related to the interpretation / emotional first followed by aspects of speech and body